Analisis Kebutuhan Pengembangan Bahan Ajar Kesetimbangan Kimia Berbasis Etnosains Terintegrasi Ekosistem Mangrove - Yuni Kurnia; Yuli Hartati; Muflihah Muflihah; Farah Erika (SAP (Susunan Artikel Pendidikan), 2026)
This study aims to analyze students' needs as a basis for developing ethnoscience-based chemistry teaching materials on chemical equilibrium by integrating the context of the mangrove ecosystem in Paser Regency, East Kalimantan. The study used a quantitative descriptive approach with a survey design of 40 grade XI students at SMA Negeri 1 Tanah Grogot through a Likert scale questionnaire compiled based on 13 indicators and grouped into four dimensions, namely the relevance of teaching materials, conceptual understanding, learning experience and technology involvement, and the integration of ethnoscience and local wisdom. The research findings indicate that the teaching materials used are still abstract and have not optimally accommodated the local context, while students show a high need for additional teaching materials and learning related to the mangrove ecosystem.. This study contributes to the development of ethnoscience-based chemistry education by demonstrating the potential of mangrove ecosystems as a local context for learning chemical equilibrium. The empirical evidence obtained provides a foundation for the development of ethnoscience-based teaching materials that can connect abstract chemical concepts with local environmental phenomena close to students' lives.